Ag2Au50(PET)36 Nanocluster: Dimeric Assembly of Au25(PET)18 Enabled by Silver Atoms. Issue 33 (4th June 2020) - Liu, Xu; Saranya, Govindarajan; Huang, Xinyu; Cheng, Xinglian; Wang, Rui; Chen, Mingyang; Zhang, Chunfeng; Li, Tao; Zhu, Yan
Abstract: The assembly of atomically precise metal nanoclusters offers exciting opportunities to gain fundamental insights into the hierarchical assembly of nanoparticles. However, it is still challenging to control the assembly of individual nanoclusters at a molecular or atomic level. Herein, we report the dimeric assembly of Au25 (PET)18 (PET=2‐phenylethanethiol), where two Au25 (PET)18 monomers are bridged together by two Ag atoms to form the Ag2 Au50 (PET)36 dimer. The Ag2 Au50 (PET)36 dimer is a unique mesomer, which has not been found in any other chiral metal nanoclusters. Furthermore, the Ag2 Au50 (PET)36 dimer is distinct from the Au25 (PET)18 monomer in its optical, electronic, and catalytic properties. This study is expected to provide a feasible strategy to precisely modulate the assembly of metal nanoclusters with controllable structures and properties. Abstract : Silver connection : The assembly of two Au25 (PET)18 monomers bridged by two Ag atoms generates the Ag2 Au50 (PET)36 dimer with distinct optical, electronic, and catalytic properties. This study provides a feasible strategy to precisely modulate the assembly of metal nanoclusters with controllable structure and properties.